Basic Statistic Using Excel 2007 for use with: Basic Statistics For Business&Economics And Statistical Techniques In Bussiness& Economics - Douglas A.Lind, William G.Marchal (McGraw Hill, 2007)
The chapter goals listed at the beginning of each chapter provides overviews of the main topics covered and the tasks students should be able to do after having worked through the chapter